Аналіз та напрями вдосконалення методів прогнозування аварійності транспортних засобів - Паснак, Іван; Колеснікова, Анна (Видавництво Львівської політехніки, 2015)
Existing methods for prediction of accident vehicles and found that they are usually based on statistical results of road accidents in previous time periods (month, year, etc.). Based on real examples are given, it is not always due to existing mathematical models possible to reliably estimate the likelihood of an accident or predict their number because each accident is primarily a random phenomenon.
Analysis and improvement areas of forecasting methods accident vehicles